Hubungan Perilaku Genitalia Hygiene dengan Kejadian Keputihan Remaja di Pondok Pesantren di Indramayu - Aeni, Wiwin Nur (Jurnal Ilmiah Kesehatan, 2017)
Leucorrhoea on teenager in Indonesia more than 70%.Leucorrhoea caused by infection of reproducitive organ, infertility, and pschycology disorder. This study was purposed to determine the correlation between genitalia hygiene with leucorrhoea events In Pondok Pesantren In Indramayu. Analitic correlation with cross sectional approach was used in this research. The sample of this study were 104 respondents, samples taken with stratified random sampling. The research instrument used questionnaire and data analized used by chi-square test. The results showed that good genitalia hygiene behavior was 54,8% and bad genitalia hygiene was 45,2%, leucorrhoea was 53,8%, not was 46,2% leucorrhoea. The result of bivariate analysis showed that p-value 1 (α = 0,05) means that there is no correlation between genitalia hygiene behavior with leucorrhoea events In Al-Ishlah Islamic Boarding School Tajug Sudimampir District Indramayu 2017. The conclusions of this study was any factors that caused leucorrhoea. Teenagers suggest to control that any factors so that can prevent the leucorrhoea. Keywords : Genitalia Hygiene, Leucorrhoea